Influence of the transferred coronavirus infection on diseases of the endocrine system in athletes - E. A. Tenyaeva; E. A. Turova; V. A. Badtieva; E. O. Okonkwo (National Electronic Information Consortium (NEICON), 2023)
Purpose: to study the effect of the transferred viral (on the example of COVID‑19) infection on the endocrine system of athletes.Materials and methods: the data of 1114 athletes (average age 22.23 ± 4.18 years) who underwent in‑depth medical examination in the period 2021-2022 were analyzed. The examination included an analysis of sports and infectious anamnesis, the results of hormonal, biochemical and instrumental studies.Results: coronavirus infection was suffered by the majority of athletes - 724 people (65 %) - in the vast majority of cases (91 %), their disease was asymptomatic or mild. 390 athletes (35 %) had no history of infection. There was a significant increase in the incidence of hypothyroidism, thyrotoxicosis, insulin‑dependent diabetes mellitus, autoimmune thyroiditis among athletes who had a coronavirus infection when compared with athletes who were not ill. The development of endocrine diseases did not depend on the severity of the infection and was most often detected with its mild and asymptomatic course. During the examination, six cases of newly diagnosed type 1 diabetes mellitus and eight cases of thyrotoxicosis were detected among athletes who had a coronavirus infection. The development of these conditions did not depend on the severity of the infection. At the same time, only 1 case of thyrotoxicosis was registered in athletes who were not ill, no new cases of type 1 diabetes mellitus were diagnosed. In the present study, no association was found between the transmitted coronavirus infection and an increase in the number of cases of nodular goiter, hyperprolactinemia and type 2 diabetes mellitus.Conclusion: the results of the study showed that in the long‑term period after COVID‑19, autoimmune endocrine diseases, such as primary hypothyroidism, diffuse‑toxic goiter with thyrotoxicosis, autoimmune thyroiditis, type 1 diabetes mellitus, were significantly more often manifested in athletes, which is probably associated with a cross‑lesion of autoimmunity against a background of viral infection.